Tropical peatland tree-species diversity altered by forest degradation - DWI ASTIANI (Society for Indonesian Biodiversity, 2016)
Astiani D. 2016. Tropical peatland tree-species diversity altered by forest degradation. Biodiversitas 17: 102-109. Indonesianexperienced relatively high deforestation and degradation. The forests degradation could bring the forests into a temporary or might bepermanent destruction not only in forest vegetation density and structure, but also in species composition. A study had been carried outto examined the impact of peatland forests degradation on their species diversity composition in Ketapang, West Kalimantan peatlandforest. Stratified random sampling was used to distinguished forest degradation class (low, intermediate and high degradation levels)Â  based on the differences in spectra image and confirmed with field checking by measuring forest canopy opening to measure thedegradation levels. Six to twelve of a 20x100m plots were established to sample tree structure and composition distributed alongpeatland landscape. All trees species diameter >5cm was registered an species identified. Results indicated that tree diversity wassignificantly reduce due to forest degradation, in low, intermediate, and high degraded forest were 82, 72, and 48 consecutively. Forestdegradation is not only resulted more than 50% of important species loss in high degraded peatland forest but also reducing 40% treeabundance. Ten species were found in high degraded forest, e.g., Calophylum inophyllum, Cyathocalyx biovulatus, Neoscortechiniakingii, and Eugenia cerina, were not present in low degraded one. The species composition and abundance shifting due to forestdegradation should be considered on peatland forest management to hinder permanent species loss.